Changes in nuclear and cytoplasmic microRNA distribution in response to hypoxic stress - Tiia A. Turunen (Nature Portfolio, 2019)
Abstract MicroRNAs (miRNAs) are small non-coding RNAs that have well-characterized roles in cytoplasmic gene regulation, where they act by binding to mRNA transcripts and inhibiting their translation (i.e. post-transcriptional gene silencing, PTGS). However, miRNAs have also been implicated in transcriptional gene regulation and alternative splicing, events that are restricted to the cell nucleus. Here we performed nuclear-cytoplasmic fractionation in a mouse endothelial cell line and characterized the localization of miRNAs in response to hypoxia using small RNA sequencing. A highly diverse population of abundant miRNA species was detected in the nucleus, of which the majority (56%) was found to be preferentially localized in one compartment or the other. Induction of hypoxia resulted in changes in miRNA levels in both nuclear and cytoplasmic compartments, with the majority of changes being restricted to one location and not the other. Notably, the classical hypoxamiR (miR-210-3p) was highly up-regulated in the nuclear compartment after hypoxic stimulus. These findings reveal a previously unappreciated level of molecular complexity in the physiological response occurring in ischemic tissue. Furthermore, widespread differential miRNA expression in the nucleus strongly suggests that these small RNAs are likely to perform extensive nuclear regulatory functions in the general case.